Age-related gene-specific changes of A-to-I mRNA editing in the human brain - Nicholas, A.; de Magalhaes, J.P.; Kraytsberg, Y.; Richfield, E.K.; Levanon, E.Y.; Khrapko, K. (Mechanisms of ageing and development, 2010)
A-to-I editing is an adenosine-to-inosine modification of mRNA particularly widespread in the human brain, where it affects thousands of genes. A growing body of evidence suggests that A-to-I RNA editing is necessary for normal development and maintenance in mammals and that its deficiencies contribute to a number of pathological states. In this study, we examined whether mRNA editing levels of two mRNA species, CYFIP2 and GABRA3, change with aging. CYFIP2 has been implicated in synaptic maintenance, while GABRA3 is a GABA receptor subunit, a part of the major inhibitory neurotransmitter system in the CNS. The levels of mRNA editing were assessed in cortex samples of 20 subjects 22–102 years old. The data show an age-dependent statistically significant decrease in editing in CYFIP2. GABRA3 editing remained much more stable with age, implying that age-related decline of RNA editing is gene-specific. This is the first report of age-dependent decline in A-to-I editing. Further examination of these and other vulnerable genes may reveal specific RNA editing mechanisms that contribute to the aging phenotype.